Eksistensi Usaha Perabot Tradisional Dalam Menghadapi Pasar Modern di Kecamatan Seunagan Timur Kabupaten Nagan Raya - Adria (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2017)
In its development, modern market in the community began to transform from traditional business to modern market. It is basically the development of the traditional business. This development emerged and developed along with the development of the economy, technology, and lifestyle of society that make people demand deeper comfort. So the need for furniture or furniture products can already be obtained in modern retail stores instantly ready for use. To find out how the existence of furniture / furniture business in the face of this modern market sat of a company required a deep understanding of how the business is run business. Therefore, this research uses qualitative method. Qualitative is more descriptive and emphasizes the depth of information. The results of the study explain the existence of a business among competitor markets should be clarified good luck about the products as well as services provided, the influence of more practical business, instant and more modern can beat the newly developed business with little capital and what is lack of good marketing promotion . Business Furniture "Business Blessings in East Seunagan District is still lacking or not able to show its existence even further. Although the development prospects will work together with one of the developers of housing, offices and other institutions in Nagan Raya area